2011
DOI: 10.3855/jidc.2269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of tuberculoid leprosy in an epidermodysplasia verruciformis patient

Abstract: Epidermodysplasia verruciformis (EV) is triggered by a variety of mechanisms that at least partly include genetic background. We present a Brazilian man with a 30-year history of flat, wart-like lesions with clinical, histopathological, and evolutive aspects consistent with papillomavirus (HPV)-associated EV. Histological analysis of the wart lesions showed epidermis with hyperkeratosis, regular acanthosis, hypergranulosis, and cells with abundant basophilic cytoplasm. Moreover, a perivascular lymphocytic infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Acquired EV (aEV) is due to an immunodeficiency secondary to immunosuppressant medications following transplant, infection with HIV, or other diseases such as systemic lupus erythematous, tuberculoid leprosy and Hodgkin lymphoma . The underlying mechanism is believed to be similar to gEV: infected cells are not cleared by the immune system because of defective cell‐mediate immunity, leading first to disseminated hyperkeratotic lesions, and then transformation to SCC and other non‐melanoma skin cancer (NMSC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquired EV (aEV) is due to an immunodeficiency secondary to immunosuppressant medications following transplant, infection with HIV, or other diseases such as systemic lupus erythematous, tuberculoid leprosy and Hodgkin lymphoma . The underlying mechanism is believed to be similar to gEV: infected cells are not cleared by the immune system because of defective cell‐mediate immunity, leading first to disseminated hyperkeratotic lesions, and then transformation to SCC and other non‐melanoma skin cancer (NMSC).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism is believed to be similar to gEV: infected cells are not cleared by the immune system because of defective cell‐mediate immunity, leading first to disseminated hyperkeratotic lesions, and then transformation to SCC and other non‐melanoma skin cancer (NMSC). Although the timing of infection and disease onset in acquired EV is variable after the onset of immunosuppression, approximately 92% of acquired EV patients develop lesions within 5 years . One study has suggested that immunosuppression regimens using azathioprine are potentially higher‐risk for EV‐development than other drug combinations .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies address the epidemiologic future of HBV infection in the general population, especially those living in small-and medium-sized cities. In these places, tertiary public hospitals have a crucial role in the Unifi ed Public Health System (SUS) for the diagnosis and treatment of infectious diseases including HIV, HBV, and HCV (5) . Our aim was to the determine the clinical, demographic, and epidemiologic characteristics of a cohort of patients diagnosed with HBV and followed up at an infectious diseases clinic of a public tertiary university hospital in the western region of State of São Paulo, Brazil.…”
mentioning
confidence: 99%